PE Ninja Warrior: Designing an American Ninja Warrior Unit for Physical Education. (2nd November 2017) - Bruno, Laura E.; Farrell, Anne
Abstract : Regular participation in physical activity during childhood and adolescence is critical to the development of healthy habits that will continue into adulthood. Research suggests that children who lead sedentary lives are more likely to continue those habits later in life. A key goal of physical education (PE) is to educate students on the importance of being physically active, as well as improve fitness levels. Recent literature suggests that school PE classes do more on this front. This has prompted the need for creative approaches in the PE classroom. PE Ninja Warrior is an example of a creative method that aims to meet the needs of today's youth. Based on the popular television show and trend, American Ninja Warrior, this article will highlight the implementation of such a program in PE, as well as identify and explain challenge course ideas.